Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/anie.202209464
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate Chelation Heals Structural Imperfections for Minimized Recombination Loss in Lead‐Free Perovskite Solar Cells

Abstract: Tin-based perovskite solar cells (Sn-PSCs) have emerged as promising environmentally viable photovoltaic technologies, but still suffer from severe non-radiative recombination loss due to the presence of abundant deep-level defects in the perovskite film and under-optimized carrier dynamics throughout the device. Herein, we healed the structural imperfections of Sn perovskites in an "inside-out" manner by incorporating a new class of biocompatible chelating agent with multidentate claws, namely, 2-Guanidinoace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 62 publications
2
63
0
Order By: Relevance
“…S7–S9†). 12,29 As depicted in Fig. 2b, the content of Sn 4+ on the surface of the pristine is relatively high and still large at the film inside, which is 37.8%, 35.1%, and 31.4%, respectively, with the increase of sputtering time.…”
Section: Resultsmentioning
confidence: 90%
“…S7–S9†). 12,29 As depicted in Fig. 2b, the content of Sn 4+ on the surface of the pristine is relatively high and still large at the film inside, which is 37.8%, 35.1%, and 31.4%, respectively, with the increase of sputtering time.…”
Section: Resultsmentioning
confidence: 90%
“…These are beneficial for shortening the carrier transport path. 24,25 Hence, their alignment minimizes the charge carrier transport length and therefore maximizes the carrier transport efficiency. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of organic molecules containing N-, S-, or O-donors has been universally acknowledged to show peculiarities in boosting efficiency and stability based on Lewis acid-base chemistry. [21][22][23][24][25][26][27][28][29][30] Recently, Hagfeldt et al discovered that a dipolar interlayer of azetidinium lead iodide (AzPbI 3 ) could increase device performance. 31 Yang et al found that tailoring the dipolar molecules to induce an extra electric eld at the heterointerface can improve the performance and stability of the device.…”
Section: Introductionmentioning
confidence: 99%